Construction management : new directions - McGeorge, W. D.; Zou, Patrick; Palmer, Angela (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
'The construction industry faces continual challenges and demands, due to market conditions and coercion by governments, for improvements in safety, quality and cost control, and in the avoidance of contractual disputes. To meet these challenges construction enterprises need to constantly seek new directions and business models in construction management. A number of tools, methods and concepts have been developed and advocated as aids to achieving improved performance, but many in the industry find them confusing or are sceptical of their relevance. The third edition of Construction Management: New Directions brings together, in a single volume, detailed discussion of a range of contemporary management concepts which are relevant to the construction industry, including strategic management; benchmarking; reengineering; partnering and alliancing; enterprise risk management; total safety management; total quality management; value management and constructability. It provides a straightforward, accessible and objective account of these concepts, showing how they interrelate and can be used to improve the performance of the construction firm.This research based text will be essential reading for industry leaders and practitioners, as well as researchers, postgraduate and senior undergraduate students.From a review of previous editionsI am in no doubt that this book will quickly become a favourite among students and practitioners alike --Construction Manager'--
'This book brings together, in a single volume, detailed discussion of a range of modern construction management concepts, and provides an objective account of these concepts, showing how they interrelate and can be used to improve the performance of the construction firm'--
Includes bibliographical references (pages [282]-295) and index.
Keywords: Construction industry -- Management